THE EFFORTS OF THE HEADMASTER IN IMPROVING THE ABILITY OF TEACHERS TO MANAGE THE LEARNING PROCESS THROUGH THE IMPLEMENTATION OF CLINICAL SUPERVISION IN SDN WONOREJO V/316 SURABAYA - Siatun Siatun (LPPM STAI Muhammadiyah Probolinggo, 2020)
Clinical supervision is a process of guidance in education that aims to assist the professional development of teachers in teaching introduction through observation and analysis of the data objectively, thoroughly, as a basis for transforming teaching behavior. In such position, the researcher aspires to conduct a class action research entitled